2009
DOI: 10.1359/jbmr.090316
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 Diabetes in Young Rats Leads to Progressive Trabecular Bone Loss, Cessation of Cortical Bone Growth, and Diminished Whole Bone Strength and Fatigue Life

Abstract: People with diabetes have increased risk of fracture disproportionate to BMD, suggesting reduced material strength (quality). We quantified the skeletal effects of type 1 diabetes in the rat. Fischer 344 and Sprague-Dawley rats (12 wk of age) were injected with either vehicle (Control) or streptozotocin (Diabetic). Forelimbs were scanned at 0, 4, 8, and 12 wk using pQCT. Rats were killed after 12 wk. We observed progressive osteopenia in diabetic rats. Trabecular osteopenia was caused by bone loss: volumetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
127
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(156 citation statements)
references
References 38 publications
(144 reference statements)
22
127
0
6
Order By: Relevance
“…As expected, T1DM led to a dramatic and significant 2-fold increase in collagen glycation. Previous studies have also reported a higher AGE accumulation in the bone matrix of diabetic animals supporting our results [14,36]. Collagen integrity was significantly lower in diabetic animals and accompanied by profound changes in tissue secondary structure.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As expected, T1DM led to a dramatic and significant 2-fold increase in collagen glycation. Previous studies have also reported a higher AGE accumulation in the bone matrix of diabetic animals supporting our results [14,36]. Collagen integrity was significantly lower in diabetic animals and accompanied by profound changes in tissue secondary structure.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies using STZ-injected rodent models have been published in the last decade and reported inconsistent data on the effect of T1DM on bone tissue material properties, i.e., the mineral and organic component of the bone matrix [12][13][14][15]. Previous studies seem suggest that bone microarchitecture deterioration appears early, while modification of intrinsic material, as determined by bone toughness, occurs later [16].…”
Section: Introductionmentioning
confidence: 99%
“…Such decreases in circulating EPCs could retard angiogenesis essential for the repair process at fracture sites. Moreover, as demonstrated by the three point bending mechanical test, DM was found to be associated with a reduction in parameters, such as bone rigidity, yield moment, ultimate moment, yield stress and energy to fracture, all of which are related to bone strength or "bone quality" [47,48] . Regarding the possible mechanisms underlying impaired mechanical properties, several investigations have demonstrated an increase in advanced glycation end products (AGE) or nonenzymatic cross-links within collagen fibers, which, in turn, lead to deterioration in the structural and mechanical properties of bone, and eventually to a decrease in bone strength [47] .…”
Section: Possible Mechanisms Of Dm-induced Osteoporosismentioning
confidence: 97%
“…The osteoporotic phenotype in T1DM mice is due to decreased osteoblast activity [14], though some studies have also reported an elevated osteoclast activity [15,16]. Diabetic mice show increasing bone loss beginning from the onset of diabetes [17] and children with early manifestation of diabetes may be at a higher risk for developing decreased cortical bone mineral density [18], indicating that the duration of diabetes may lead to the increase progression of bone loss and fracture risk later in adulthood.…”
Section: Overview Of Diabetes and Bonementioning
confidence: 99%
“…Once diabetes become too severe, insulin treatment is required for these mice to prevent complications of diabetes and death. Due to the low frequency rate of NOD males developing diabetes and the non-synchronous onset of diabetes, this may lead to a wide range of responses, especially since the effects on bone proceeds to worsens due to the length time of hyperglycemia [17]. Both STZ mice and NOD mice have significant weight loss, hyperglycemia, and elevated adipocytes within the bone marrow, with NOD mice displaying a more severe phenotype than STZ mice.…”
Section: Type 1 Diabetic Mellitus Animal Modelsmentioning
confidence: 99%